An exploratory study of Ijarah accounting practices in Malaysian financial institutions - Mohd. Shariff, Ros Aniza; Abdul Rahman, Abdul Rahim (Centre fo r Indonesian Accounting and Management Research, Brawijaya University, 2005)
Prior studies on Ijarah were mainly focusing on the economics, legal and ﬁnancial aspects, there was, however, so far no in- depth study on accounting for Ijarah. The main objective of this study is to explore the nature of accounting practices as practiced by Malaysian ﬁnancial institutions. First, the study makes comparison between the Intemational Accounting Standard on leasing (IAS 17); the accounting standard for Ijarah (FAS 8) as developed by the Accounting and Auditing Organization for lslamic Financial Institutions (AAOIFI); and the Malaysian Accounting Standard Board (MASB 10). The study found that there are major differences as to the nature of leasing and Ijarah, and as a result accounting principles that have driven all the three standards as well as accounting techniques developed for leasing and Ijarah are signiﬁcantly different. Secondly, the study examines the level of acceptability of the AAOlFI's FAS 8 among the Malaysian ﬁnancial institutions. The result of the questionnaire survey shows a low level of acceptability of FAS 8 and the result from the interviewsurvey further conﬁrms this ﬁnding. This study indicates, subject to further studies on other lslamic ﬁnancial instruments and other lslamic countries, that the effort to harmonise the accounting practices on lslamic ﬁnancing practices by ﬁnancial institutions Internationally may be a difficult task. Secondly, until and unless the AAOIFI standard is adopted by the regulatory agency as in the case of Malaysia, Bank Negara Malaysia, AAOIFI standards will remain only as a reference but do not have the legal authority. Consequently, the quality and comparability of accounting information of lslamic ﬁnancing such as Ijarah will be seriously at a stake.